INFLIXIMAB and ADALIMUMAB in Uveitic Macular Edema. (3rd October 2018) - Lejoyeux, R.; Diwo, E.; Vallet, H.; Saadoun, D.; Tezenas du Montcel, S.; Bodaghi, B.; LeHoang, P.; Fardeau, C.
ABSTRACT: Purpose: To compare the efficacy of infliximab and adalimumab in patients with refractory uveitis-related macular edema (ME). Methods: A retrospective study was conducted in all patients with refractory uveitis-related ME treated with infliximab or adalimumab in Pitié-Salpêtrière hospital between January 1, 2006 and January 1, 2016. All patients underwent a complete ophthalmologic examination, OCT and retinal angiography at baseline, and 6 (M6) and 24 months (M24) after treatment initiation. Main outcome was a decrease in central foveal thickness (CFT) on OCT. Results: Twenty-five patients were included: 12 treated with adalimumab and 13 treated with infliximab. The median baseline CFT was 381 μm (Q1 = 254; Q3 = 470) in the adalimumab group and 469 μm (307; 539) in the infliximab group. At M6, 6/12 adalimumab-treated patients (50%) and 8/13 infliximab-treated patients (61%) were responders. The median CFT decrease from baseline was 61 μm (17–136) and 66 μm (−59–119) respectively at M6 and M24 in the adalimumab group versus 92 μm (9–165) and 52 μm (33–130) respectively at M6 and M24 in the infliximab group (all p > 0.05). Conclusion: No significant difference in efficacy was observed between infliximab and adalimumab at M6 and M24.